2022
DOI: 10.1371/journal.pone.0265275
|View full text |Cite
|
Sign up to set email alerts
|

External validation of cardiac arrest-specific prognostication scores developed for early prognosis estimation after out-of-hospital cardiac arrest in a Korean multicenter cohort

Abstract: We evaluated the performance of cardiac arrest-specific prognostication scores developed for outcome prediction in the early hours after out-of-hospital cardiac arrest (OHCA) in predicting long-term outcomes using independent data. The following scores were calculated for 1,163 OHCA patients who were treated with targeted temperature management (TTM) at 21 hospitals in South Korea: OHCA, cardiac arrest hospital prognosis (CAHP), C-GRApH (named on the basis of its variables), TTM risk, 5-R, NULL-PLEASE (named o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…To our knowledge, this study is the third external validation of the PROLOGUE score overall and the second one performed in Europe [ 30 , 31 ]. Our findings are in line with the other European validation study performed in Austria, in which the score showed an AUROC of 0.82 (95% CI 0.80 to 0.85) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, this study is the third external validation of the PROLOGUE score overall and the second one performed in Europe [ 30 , 31 ]. Our findings are in line with the other European validation study performed in Austria, in which the score showed an AUROC of 0.82 (95% CI 0.80 to 0.85) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two of the most promising and thoroughly validated scoring models for the prognostication of neurological outcome after cardiac arrest are the Out-of-Hospital Cardiac Arrest (OHCA) and the Cardiac Arrest Hospital Prognosis (CAHP) scores [ 9 , 11 13 ]. Both of these scores have shown good prognostic accuracy in numerous previous validations [ 13 30 ]. A drawback of both models is the fact that they require no-flow time, which is often inaccurate or unknown, especially if the cardiac arrest was unwitnessed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the calibration assessment in the external validation of several previous prediction models for patients with cardiac arrest with ROSC tended to overestimate poor outcomes. [33][34][35] In other words, accurate assessment by our models would decrease premature WLST in patients who could otherwise have achieved favourable neurological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…31 The authors reported excellent discrimination ability (AUC ¼ 0.81) for predicting favorable outcome (CPC: 1-2) at discharge, which was similar in an independent 1,163-patient cohort (AUC ¼ 0.77). 32…”
Section: C-graph Scalementioning
confidence: 99%